Dietary preference of key microhabitat Diadema setosum: a step towards holistic Banggai cardinalfish conservation. (February 2019) - Moore, A; Ndobe, S; Ambo-Rappe, R; Jompa, J; Yasir, I
Abstract: The sea urchins Diadema setosum and D . savignyi are key symbionts of the Banggai cardinalfish Pterapogon kauderni, a species of global and national conservation concern. There is growing interest in Diadema propagation for conservation and human consumption; however little is known about the dietary preferences of Indo Pacific Diadema species. This study explored the feeding preference of Diadema setosum offered a choice of two macroalgae ( Ulva reticulata, Gracilaria sp.) and two seagrasses ( Thalassia hemprichii, Enhalus acoroides ). Portions (5g) of the four feeds were attached to the corners of rectangular plastic cages and one D . setosum released in the centre of each cage. Uneaten feed was weighed after 24 hours. This procedure was repeated for 5 days with 8 replicates. Mean daily feed consumption/urchin was 4.31g, . All urchins ate a varied diet comprising all four feed types, with a significant preference (p < 0.01) for macroalgae (on average 80%). Our results point to an important role of D . setosum in macroalgal control; however this urchin might graze on cultivated seaweeds. Further research avenues include the use of macroalgae in prepared feeds for Diadema culture, including in the context of P . kauderni microhabitat rehabilitation.